2017
DOI: 10.1094/pdis-03-16-0298-re
|View full text |Cite
|
Sign up to set email alerts
|

Equal Distribution of Mating Type Alleles and the Presence of Strobilurin Resistance in Algerian Zymoseptoria tritici Field Populations

Abstract: Zymoseptoria tritici, the causal agent of septoria tritici blotch, is an important wheat pathogen responsible for high yield losses worldwide. The assessment of the distribution of both mating type idiomorphs was studied in several wheat-growing areas in North Algeria. Both mating types occurred at all spatial scales tested and showed an equal frequency distribution at the country level, with 53% for Mat1-1 and 47% for Mat1-2. At finer scales, co-occurrence of both mating types was found in 38% of leaves analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Recent research increased the general understanding of the Z. tritici epidemiology in the Maghreb. Hamada [ 17 ] reported the occurrence of the teleomorph of the fungus in Tunisia, despite the arid conditions in the region, and Neddaf et al [ 18 ] determined an equal distribution of both mating types in Algeria, indicating regular sexual reproduction, which likely contributes to the vast genetic diversity in this region. Similar results have recently been reported in Tunisia on durum wheat [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research increased the general understanding of the Z. tritici epidemiology in the Maghreb. Hamada [ 17 ] reported the occurrence of the teleomorph of the fungus in Tunisia, despite the arid conditions in the region, and Neddaf et al [ 18 ] determined an equal distribution of both mating types in Algeria, indicating regular sexual reproduction, which likely contributes to the vast genetic diversity in this region. Similar results have recently been reported in Tunisia on durum wheat [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have recently been reported in Tunisia on durum wheat [ 19 ]. The use of fungicides has been more slowly adopted by durum wheat growers as compared to bread wheat producers in Europe, and the first occurrence of strobilurin resistance have been reported in Tunisia and Algeria [ 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycosphaerella graminicola ) is considered to be one of the major diseases affecting both durum and bread wheat in Algeria. Algerian Z. tritici populations undergo frequent sexual reproduction mirrored by cooccurrence of both mating types (Allioui et al , 2014; Meamiche Neddaf et al , 2017). Pseudothecia have been obtained under controlled conditions (Ayad et al , 2014), however the natural occurrence of the teleomorph stage has never been reported in the country.…”
Section: Figurementioning
confidence: 99%